How Raven Marked the Land When the Earth Was New - Fienup-Riordan, Ann (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2017)
In Alaska, Raven is paradoxically both a lazy scavenger, relying on others to hunt for it and not adverse to eating human flesh, and the creator of light and life. Raven in southwest Alaska is also known as the creator of many landforms seen to this day, including mountains, rivers, and islands. Although Raven stories are told throughout the eastern Arctic as well as interior Alaska, specific places are rarely named in these tales. In contrast, Yup’ik narrators continue to refer to particular places, all across southwest Alaska, where Raven and his daughter left marks on the landscape, while recalling their activities in the distant past.